The role of international accounting and auditing standards in business risk and business continuity (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The business risks faced by enterprises are considered the most important current risks that develop with the rapid changes that occur in the business environment, including the global competition, the opening of markets, different tastes, technological development, spread of fraud, imitation of products, changes in prices and other matters. And prevent the enterprises from achieving their strategic objectives, as well as return to the audit profession to fail despite the care of the crisis and a clean report on the financial statements and financial situation, and therefore focused this research on the risks of business and its impact on continuity, The international accounting and auditing standards address the business risks directly and directly because of their highimportance, and one of the main conclusions of the research is that the interest in business risks directly by the standards of auditing and accounting international and make it a key paragraphs helps to maintain the continuity of the establishment andoccupation The research recommended that business risks should be directly addressed by the international accounting and auditing standards and analyzed and evaluated when planning the audit to avoid failure due to rapid business failures because of the riskssurrounding.